2011
DOI: 10.1177/0891242411408292
|View full text |Cite
|
Sign up to set email alerts
|

Policy Versus Place Luck: Achieving Local Economic Prosperity

Abstract: This research focuses on the relative impact of place luck and economic development policy in contributing to long-term economic growth. Using a unique national data set composed of surveys of public officials, three decades of census data, and a variety of other data covering climate, health, amenities, and so on, the following research questions are addressed: (a) Is economic prosperity better explained by local development policy or simple place luck? (b) Are particular economic development policies more st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 64 publications
3
47
0
Order By: Relevance
“…While Scranton, as a small city, enjoys not having many “big city” problems, its extreme decline in the past few decades shows that, without continued investments in infrastructure, public schools and parks, neighborhoods, and (most importantly for a small city) the downtown, Scranton may lose its revitalization momentum. As Reese and Ye (2011) found in their investigation of local economic development policies, Scranton's development projects (such as KOZs or a downtown shopping mall) may not prove to foster economic regional growth or revitalize Scranton's downtown. Rather, the quality of life that Scranton offers is a major attraction to current and potential residents, in contrast to its branding as a “cool” place or as an economic center.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While Scranton, as a small city, enjoys not having many “big city” problems, its extreme decline in the past few decades shows that, without continued investments in infrastructure, public schools and parks, neighborhoods, and (most importantly for a small city) the downtown, Scranton may lose its revitalization momentum. As Reese and Ye (2011) found in their investigation of local economic development policies, Scranton's development projects (such as KOZs or a downtown shopping mall) may not prove to foster economic regional growth or revitalize Scranton's downtown. Rather, the quality of life that Scranton offers is a major attraction to current and potential residents, in contrast to its branding as a “cool” place or as an economic center.…”
Section: Resultsmentioning
confidence: 99%
“…Quality of life investments (in schools, parks, public spaces, etc.) are also related to economic growth in city regions (Reese & Ye, 2011). So it is not surprising that in this study interviewees mentioned “quality of life” as the best aspect of living in the Scranton area.…”
Section: Social Capital and Revitalizationmentioning
confidence: 99%
“…In order for us to identify the effect of the IFT abatement program, it is important to control for other fiscal policy influences on industrial property value growth. In the present study, we use school spending to control for other local services since research has indicated that the quality of local public schools is a particularly important factor in local economic health (Gottlieb, ; Reese & Ye, ; Wrigley & Lewis, ). We also control for the number of crimes per 1,000 to capture temporal unobservable shocks to the quality of life, which may be correlated with industrial property value growth.…”
Section: Methodsmentioning
confidence: 99%
“…The creative class is attracted to areas with a higher quality of life (Florida, 2002;Reese & Ye, 2011), so areas with more natural amenities may attract more entrepreneurs. These locations may already have higher business activity (Henderson et al, 2007;Henderson & Weiler, 2010) and, thus, offer opportunities for networking and innovation.…”
Section: Natural Amenities Scalementioning
confidence: 99%